Internal Engagement of Members of the Palembang City Arts Council and Its Implications for Traditional Arts Management - Akbariansyah Akbariansyah; Muhsin Ilhaq; Triningsih Triningsih; Syafwatul Putria Hidayatullah; Jamilah Jamilah (Peneliti.net, 2026)
This study aims to examine the dynamics of internal engagement among members of the Palembang City Arts Council in managing traditional arts. It focuses on understanding how internal engagement shapes organizational effectiveness, decision-making processes, and the sustainability of traditional arts within a local cultural institution context. This study used a qualitative approach with a case study strategy. Data were collected through semi-structured in-depth interviews with council members, participatory observation of organizational activities, and document analysis of programs and policy outputs. The collected data were analyzed using thematic analysis to identify patterns of internal engagement. The findings reveal that internal engagement among members is uneven and largely administrative or symbolic. Engagement is influenced by institutional structure, clarity of roles, internal communication patterns, and resource limitations. Higher levels of engagement are associated with stronger collaboration, greater program innovation, and more effective management of traditional arts. This study is applicable to the fields of arts management, cultural governance, and organizational studies. The findings may serve as a reference for local arts councils, cultural institutions, and policymakers in strengthening internal governance mechanisms and improving the sustainability of traditional arts at the regional level. This study introduces internal engagement as a key non-technical factor in traditional arts management. It shifts the analytical focus from artistic preservation to institutional dynamics, offering new insights into how internal organizational processes influence the effectiveness and sustainability of local cultural institutions in Indonesia.